2018
DOI: 10.1190/geo2016-0445.1
|View full text |Cite
|
Sign up to set email alerts
|

Common-reflection-surface-based prestack diffraction separation and imaging

Abstract: Diffraction imaging can lead to high-resolution characterization of small-scale subsurface structures. A key step of diffraction imaging and tomography is diffraction separation and enhancement, especially in the full prestack data volume. We have considered point diffractors and developed a robust and fully data-driven workflow for prestack diffraction separation based on wavefront attributes, which are determined using the common-reflection-surface (CRS) method. In the first of two steps, we apply a zero-off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 59 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…For that reason, accessing the diffracted wavefield has been and still remains a major challenge to confront. In recent years, a range of methods has been introduced to arrive at approximate diffraction‐only images based, e.g., on modified versions of Kirchhoff's diffraction integral (e.g., Dafni & Symes, 2017; Moser & Howard, 2008; Yin & Nakata, 2017), specific versions of the Radon transformation and plane‐wave destruction filters (e.g., Fomel, 2002; Karimpouli et al, 2015), or multidimensional stacking (Bakhtiari Rad et al, 2018; Bauer et al, 2016; Dell & Gajewski, 2011). While the latter has the advantage of being directly applicable in the time domain without the need for specific data transformations and not requiring a detailed velocity model, the quality of the separation depends on the quality of the performed coherence measurements and the prestack data.…”
Section: Methodsmentioning
confidence: 99%
“…For that reason, accessing the diffracted wavefield has been and still remains a major challenge to confront. In recent years, a range of methods has been introduced to arrive at approximate diffraction‐only images based, e.g., on modified versions of Kirchhoff's diffraction integral (e.g., Dafni & Symes, 2017; Moser & Howard, 2008; Yin & Nakata, 2017), specific versions of the Radon transformation and plane‐wave destruction filters (e.g., Fomel, 2002; Karimpouli et al, 2015), or multidimensional stacking (Bakhtiari Rad et al, 2018; Bauer et al, 2016; Dell & Gajewski, 2011). While the latter has the advantage of being directly applicable in the time domain without the need for specific data transformations and not requiring a detailed velocity model, the quality of the separation depends on the quality of the performed coherence measurements and the prestack data.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to previously proposed strategies (e.g. Berkovitch et al, 2009;Dell and Gajewski, 2011;Bakhtiari Rad et al, 2018) which directly target the weak diffracted wavefield, a conventional reflection stack is suggested, followed by its subsequent adaptive subtraction from the full input wavefield,…”
Section: Coherence and Wavefrontsmentioning
confidence: 99%
“…While some approaches introduced a diffraction bias in the migration scheme (Khaidukov et al, 2004;Moser and Howard, 2008;Klokov and Fomel, 2012), other strategies aim to extract the weak diffraction response in a separate step before imaging (e.g. Bansal and Imhof, 2005;Fomel et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise applied before migration, there are some techniques that make direct use of wave-field coherence for diffraction separation (Berkovitch et al, 2009;Dell and Gajewski, 2011;Bauer et al, 2016;Bakhtiari Rad et al, 2018). While these methods specifically target the diffracted wave field for extraction, recent developments have shown that a more surgical, amplitude-preserving separation can be achieved by assessing the coherence of reflections instead (Schwarz and Gajewski, 2017a;Schwarz, 2019b).…”
Section: Introductionmentioning
confidence: 99%